The law on domestic violence in Malaysia - Randawar, Daleleer Kaur; Mohd Zin, Najibah (IIUM Press, 2019)
The Law on domestic violence in Malaysia discusses on domestic violence related to Muslims and non-Muslims in Malaysia which is generally based on the Domestic Violence Act 1994 and several other supplementary statutes. With the changes in the law in this area, it is important that the book reflects the latest amendments and developments, whether they be statutory or case law. This book clearly explains the legal principles governing Domestic Violence in providing protection towards the victims. Reference is also made to other related legislation pertaining to domestic violence which impact on the functioning of family law. The analysis and the discussion provided by the authors will assist readers to grasp the basic as well as the more intricate aspects of domestic violence. Comparison with certain selected jurisdiction is made to provide an insight and suggest necessary reforms to suit the modernization of communities and the changing society. The book intends to provide invaluable resource for scholars, students, researchers and practitioners regarding the law on domestic violence in Malaysia and some selected jurisdictions.